(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Jugular foramen tumor is a rare tumor. Jugular foramen schwannoma is rarer. This type of tumor may present in combination of different cranial nerve palsies in the form of different syndromes or may also be diagnosed incidentally. Management of such tumor is not straight forward. Case reports: Two young male presented with headache, vomiting, gait instability, right sided hearing loss. Clinically they had different cranial nerves dysfunction. Imaging showed jugular foramen tumor extending from posterior fossa to almost common carotid bifurcation at neck in both cases. Near total microsurgical excisions of the tumor were done through retrosigmoid suboccipital plus transmastoid high cervical approach with facial nerve mobilization in one case and without mobilization in other case. In case 1 combination of lower cranial nerve palsies is unique with inclusion of VIII nerve and that does not belong to any of the jugular foramen syndromes (i.e. Vernet, Collet- Sicard, Villaret, Tapia, Schmidt, and Jackson). Here IX, X, XI, XII and VIII cranial palsies was present (i.e.Collet-Sicard syndrome plus VIII nerve syndrome!). In the second case there was IX & X dysfunction with VIII dysfunction. We also went through the short review of the literature here DOI: http://dx.doi.org/10.3329/bjo.v18i2.12015 Bangladesh J Otorhinolaryngol 2012; 18(2): 183-192